The Aesthetic Of Tenun Pahang Patterns - Norbayanti binti Abu Bakar; Jamal Rizal Razali (FKIP, Universitas Palangka Raya, 2023)
This paper will discuss the aesthetic of patterns used in Tenun Pahang (TP). This study also aims to describe the patterns found in TP, both basic and contemporary modern patterns. This handicraft product originates from Keladi Island, Pahang. TP is said to be originated from Sulawesi which was brought to Malaya almost 200 years ago. Based on observations, there are various designs used by weavers as the background of this product. In the field study conducted, 2 (two) informants were interviewed and they are from the Royal Pahang Institute of Weaving Skills, Pahang State Crafts and the eleventh (11) generation of Karaeng Aji descendants who are said to have brought this weaving skill to Keladi Island. The results of the analysis found that the pattern used as a background on this TP product was inspired by the high creativity of the weavers as well as the beauty of the production of the TP pattern which is close to the culture of life of the Pahang people themselves. This study is important for the overall understanding as well as a clearer translation of the patterns found in TP.